Food Practices, Consumerism, and Cultural Identity in Dutch and Nepali Families - Paudel, Saraswati; Paudel Scholte, Marije Hester Johanna (HPE Forum, 2026)
This study investigates the relationships between food practices, consumerism, and cultural identity within Dutch and Nepali families. Through semi-structured interviews with 12 families (6 from each cultural context), provides a rich, comparative analysis of how daily food-related activities, shopping, cooking, and eating are shaped by and, in turn, shape cultural values, global market forces, and notions of family cohesion. The primary objectives are to document and analyze daily food practices, explore the cultural meanings attached to food, investigate the influence of globalized consumerism, understand family negotiation strategies, and compare the findings to develop a richer theoretical model. Thematic analysis revealed a stark contrast: Dutch families exhibit a highly pragmatic, efficient, and individualistic ‘Food as Fuel’ paradigm, viewing meals through a lens of logistical management and conscious consumption. In contrast, Nepali families demonstrate a holistic, relational, and ritualistic ‘Food as Love’ paradigm, where food is a core medium for expressing love, maintaining tradition, and reinforcing social bonds. Despite these divergent cultural logics, both groups actively navigate the pressures of global consumerism, with Dutch families leveraging it for convenience and ethical distinction, while Nepali families engage with it as a means of cultural preservation and status negotiation. This study concludes that the kitchen remains a vital, dynamic arena where global and local forces converge, and family identities are continuously cooked, consumed, and redefined.